2019
DOI: 10.1007/s10877-019-00428-3
|View full text |Cite|
|
Sign up to set email alerts
|

Multicenter comparison of three intraoperative hemoglobin trend monitoring methods

Abstract: Transfusion decisions are guided by clinical factors and measured hemoglobin (Hb). Time required for blood sampling and analysis may cause Hb measurement to lag clinical conditions, thus continuous intraoperative Hb trend monitoring may provide useful information. This multicenter study was designed to compare three methods of determining intraoperative Hb changes (trend accuracy) to laboratory determined Hb changes. Adult surgical patients with planned arterial catheterization were studied. With each blood ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“… 21 However, a recent multicenter study showed that the Hb accuracy mean bias for SpHb was 0.24 g/dL. 22 In vivo SpHb adjustment, which was used in this study, improved the accuracy of SpHb. 23 , 24 For a timely blood transfusion, the trending capability of SpHb is important, and it more accurately estimates the appropriate timing for invasive Hb measurements than do clinicians.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“… 21 However, a recent multicenter study showed that the Hb accuracy mean bias for SpHb was 0.24 g/dL. 22 In vivo SpHb adjustment, which was used in this study, improved the accuracy of SpHb. 23 , 24 For a timely blood transfusion, the trending capability of SpHb is important, and it more accurately estimates the appropriate timing for invasive Hb measurements than do clinicians.…”
Section: Discussionmentioning
confidence: 68%
“… 23 , 24 For a timely blood transfusion, the trending capability of SpHb is important, and it more accurately estimates the appropriate timing for invasive Hb measurements than do clinicians. 22 , 25 - 27 However, SpHb monitoring is still controversial for postoperative management. It was reported to be unsuitable to maintain the Hb level >8 g/dL, particularly in those with lower Hb levels in the intensive care unit.…”
Section: Discussionmentioning
confidence: 99%
“…1.4% groups has been demonstrated in human or veterinary patients (Miller et al 2011;Tayari et al 2021). A central exclusion zone for a change in [Hb] values of ± 0.5 g dL e1 was applied to rule out pairs of data with minimal difference (Applegate et al 2020). For the four-quadrant plot, the change in [Hb] measured by the reference method was plotted against the change in [Hb] measured by the test method in a regression style.…”
Section: Discussionmentioning
confidence: 99%
“…Our exclusion zones were defined based on 95% LoA, meaning that a change up to ± 0.5 g dL e1 may not reflect a real change in circulating haemoglobin measured. However, as the limits of the exclusion zone are arbitrarily defined, either based on absolute values or by percentage change (e.g., 10% or 15%), this could differ in other settings or when using different analysers and may present a limitation (Saugel et al 2015;Applegate et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In this edition of JCMC, Applegate et al demonstrate that the improvement in technology in pulse oximetry is advancing the trend accuracy of non-invasive hemoglobin (SpHb) measurement [1]. This will hopefully lead to the end of the "stat" bring back to the operating room at 7 am in the morning of patients, when the routine morning laboratory results are reviewed.…”
mentioning
confidence: 99%